МЕТОДОЛОГІЯ МЕТРИЧНОГО ВИМІРЮВАННЯ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ: modeling, professional competence, acquirer, metric measurement (Innovative professional education, 2022)
The article considers the problem of modeling and measuring thecompetence of professional competence of software applicants; substantiation of thepragmatic methodology of metric measurement of the level of PR as a professionalstandard of the corresponding qualification, which is sufficient to fulfill the tasks of therelevant actual professional activity according to its quality standard
Keywords: modeling, professional competence, acquirer, metric measurement